Eosinophilic bronchitis: clinical features, management and pathogenesis. - Birring, S; Berry, M; Brightling, C; Pavord, I (2003)
Eosinophilic bronchitis is a common and treatable cause of chronic cough. The major pathological feature is eosinophilic airway inflammation, similar to that seen in asthma. However, the associated airway dysfunction is quite different, with evidence of heightened cough reflex sensitivity, but no variable airflow obstruction or airway hyperresponsiveness. Recent evidence suggests that the differences in functional association are related to differences in localization of mast cells in airway wall, with airway smooth muscle infiltration occurring in asthma and epithelial infiltration in eosinophilic bronchitis. Diagnosis is usually made with induced sputum analysis after exclusion of other causes for chronic cough on clinical, radiological and lung function assessment. The cough responds well to inhaled corticosteroids but dose and duration of treatment remain unclear. Little is known about the natural history of this condition. However, some patients with COPD without a history of previous asthma have sputum eosinophilia, so one possibility is that some cases of eosinophilic bronchitis may develop fixed airflow obstruction. Further study of this interesting condition will increase our understanding of airway inflammation and airway responsiveness, leading to novel targets for therapeutics for both eosinophilic bronchitis and asthma.